CAE design and failure analysis of automotive composites - Lu, Y. Charles; Pilla, Srikanth (PT (Series) (Warrendale, Pa.), 2015)
This publication focuses on the latest use of CAE (Computer-Aided Engineering) methods in design and failure analysis of composite materials and structures, beginning with a brief introduction to the design and failure analysis of composite materials, and then presenting some recent, innovative CAE design examples of composite structures by engineers from major CAE developers and automobile OEMs and suppliers. This title brings together 12 SAE technical papers, carefully selected by the editors covering three main areas of expertise: Design and failure analysis of composites: static loading; Design and failure analysis of composites: Dynamic and impact loading; Design and failure analysis of composites: blast loading.